Havia um oceano no fim do caminho: aspectos da literatura fantástica de Neil Gaiman - Santana, Erick Torres (2018)
This work aims to investigate the fantastic aspects presented in the book The Ocean at the end of the path, by the British writer Neil Gaiman, through their symbolic relations. Our theoretical foundations are based mainly on the works of Tzvetan Todorov (2014), Flávio Garcia (2007), Jean Paul Sartre (1968) David Roas (2014) and Farah Mendlesohn (2008),offering criteria for interpretative and analytical development. It was also sought to identify possible contributions to the construction of a meaning of the world through narratives that permeate the human journey, as the mythical ones in anthropology, psychology and literary criticism. Finally, we warn that this work does not propose a final definition about the concepts of fantastic, but we want it to offer directions in this vast ocean of possibilities proposed by literature